Training on bioethics in dentistry curriculum from the perspective of students - Zaror Sánchez, Carlos; Muñoz Millán, Patricia; Espinoza Espinoza, Gerardo; Vergara González, Carolina; Valdés García, Patricio (Acta Bioethica, 2014)
A descriptive study was carried out through content analysis, with the goal of knowing the perceptions of dentistry students about bioethics training in Dentistry curriculum of Frontera University. Data collected was carried out through focal group technique in two sessions of 12 students each, represented by two students from de different levels of the career. The interrelation among participants was stimulated through a guide for conduction previously designed. Data registered through tape recording were transcribed for content analysis, carried out manually by triangulation among researchers. Several categories were established by content analysis of primary data, grouped in four big dimensions: concept of bioethics, importance of bioethics in professional exercise, teaching-learning of bioethics and modality of teaching of bioethics. Dentistry students of Frontera University walked in assertive way through issues belonging to the complex dimension of bioethics training and recognize the importance of bioethics in their training.